Association between polymorphism rs2421943 of the insulin-degrading enzyme and schizophrenia: Preliminary report - Ambrozová, Laura; Zeman, Tomáš; Janout, Vladimír; Janoutová, Jana; Lochman, Jan; Šerý, Omar (Journal of clinical laboratory analysis, 2023)
BACKGROUND: Insulin-degrading enzyme (IDE) is an important gene in studies of the pathophysiology of type 2 diabetes mellitus (T2DM). Recent studies have suggested a possible link between type 2 diabetes mellitus (T2DM) and the pathophysiology of schizophrenia (SZ). At the same time, significant changes in insulin-degrading enzyme (IDE) gene expression have been found in the brains of people with schizophrenia. These findings highlight the need to further investigate the role of IDE in schizophrenia pathogenesis. METHODS: We enrolled 733 participants from the Czech Republic, including 383 patients with schizophrenia and 350 healthy controls. Our study focused on the single nucleotide polymorphism (SNP) rs2421943 in the IDE gene, which has previously been associated with the pathogenesis of Alzheimer's disease. The SNP was analyzed using the PCR-RFLP method. RESULTS: The G allele of the rs2421943 polymorphism was found to significantly increase the risk of developing SZ (p < 0.01) when a gender-based analysis showed that both AG and GG genotypes were associated with a more than 1.55 times increased risk of SZ in females (p < 0.03) but not in males. Besides, we identified a potential binding site at the G allele locus for has-miR-7110-5p, providing a potential mechanism for the observed association. CONCLUSION: Our results confirm the role of the IDE gene in schizophrenia pathogenesis and suggest that future research should investigate the relationship between miRNA and estrogen influence on IDE expression in schizophrenia pathogenesis.
Keywords: Insulysin; insulinasa; Male; insulin-degrading enzyme (IDE); Genotype; single nucleotide polymorphism (SNP); Schizophrenia; Alzheimerova nemoc; Alzheimer Disease; Diabetes Mellitus, Type 2; mužské pohlaví; jednonukleotidový polymorfismus; diabetes mellitus 2. typu; candidate gene analyses; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; Humans; schizophrenic disorder; schizofrenie; genotyp; miRNA; genetic association study; Female